2013
DOI: 10.3109/09638237.2013.779368
|View full text |Cite
|
Sign up to set email alerts
|

Family members' of persons living with a serious mental illness: Experiences and efforts to cope with stigma

Abstract: Findings suggest that families learn from their own experience the "art of selective disclosure": what, when, how much and who to share information with. Coping strategies are developed based on the situation and family members' needs and personal resources which differ between families and over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 17 publications
3
54
0
7
Order By: Relevance
“…Otro aspecto a destacar de nuestros resultados, es que parecen indicar que las estrategias de afrontamiento familiar negativas son más habituales en ciertos acontecimientos estresantes como son los accidentes (17) , discapacidades (8) , enfermedades mentales (25,27,31,36) y adicciones (22,26) . Siendo las estrategias de afrontamiento más utilizadas la evitación, la negación y la ocultación del problema.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Otro aspecto a destacar de nuestros resultados, es que parecen indicar que las estrategias de afrontamiento familiar negativas son más habituales en ciertos acontecimientos estresantes como son los accidentes (17) , discapacidades (8) , enfermedades mentales (25,27,31,36) y adicciones (22,26) . Siendo las estrategias de afrontamiento más utilizadas la evitación, la negación y la ocultación del problema.…”
Section: Discussionunclassified
“…Así mismo, según otros autores, estos tipos de estrategias están encaminadas a disminuir la alteración emocional que provoca una situación estresante de la cuál piensan que no pueden hacer nada para modificarla (40) . Por ello, ocultar la enfermedad mental, la adicción o la discapacidad de algún miembro de la familia tiene como finalidad defenderse frente al estigma, ya que esto conlleva un gran coste emocional a nivel familiar, debido a las alteraciones que provoca estas situaciones en la salud familiar y en sus diferentes dimensiones, las relaciones familiares y las redes sociales de esta (22,25) . En cambio, Lazarus (41) afirma que el uso de este tipo de estrategias de afrontamiento a veces puede preceder a la utilización de estrategias de afrontamiento centradas al problema y que conlleven a la supervivencia de la familiar en el tiempo.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…At the same time, stigmas and discrimination are also common among families, who share similar beliefs about inferiority and may feel a lessened sense of humanity [6]. Other research also has shown that family members of serious mental health consumers, especially caregivers of patients with schizophrenia, often encounter stigma and discrimination [4], [7]–[10]. Family stigma negatively impacts caregivers and persons with schizophrenia, creating burdens, enhancing stress and affecting the quality of life [11].…”
Section: Introductionmentioning
confidence: 99%
“…Negative comments and behaviors from others, including extended family members, created feelings of rejection and shame and further contributed to emotional distress among caregivers. These feelings of rejection indicate that families may experience social isolation that can add to their subjective burden (Karnieli-Miller et al, 2013; Larson & Corrigan, 2008). Although caregivers may subscribe to strong views on family interdependence, they may experience limited support from their extended family and therefore be vulnerable to increased burden (Hackethal et al, 2013).…”
Section: Discussionmentioning
confidence: 99%